SA’DULLA SIYOYEVNING “AHMAD YASSAVIY” ROMANIDA ONA OBRAZI - Sapayeva, F.D.; Matchanova, K.S. (SCIENCE and SOCIETY, 2024)
The article talks about the special features of the “Weeping Mother” season in the novel “Ahmed Yassavi” by the writer Sa’dulla Siyoyev, who conducted worthy creative researches in Uzbek literature and created his own school. It is analyzed that in Sadulla Siyoyev’s work, he reveals the aesthetic principles of the writer in harmony between historicity, humanity, nationality, interpretation of feelings and spirituality, and social events, images.
Keywords: Sa’dulla Siyoyev; belles-lettres; novel; history; humanity; mother; “Ahmad Yassaviy”; “Yig‘lama Onaizor”; Makka; Shaykh